OZONIOTHERAPY: A THERAPEUTIC APPROACH FOR THE TREATMENT OF FIBROSIS AFTER SUBMENTAL LIPOPLASTY - Carolina Alcântara de Oliveira, Érika; Rech Feldmann, Cristina (Health and Society, 2022)
In recent years there has been a significant increase in the demand for aesthetic procedures aimed at Orofacial Harmonization, attracting both men and women. An integral component of facial rejuvenation is the restoration of an aesthetic neck contour. To treat this, the localized fat accumulation is removed through the aesthetic procedure of liposuction surgery, leading to an improvement in the facial contour. Fat removal is done using cannulas. Small incisions are made in the skin, where the cannulas will be introduced and will aspirate the localized fats through negative pressure. Liposuction, as with any surgical procedure, can have complications. Fibrosis is one of the main ones, being a direct consequence of post-injury repair. A complementary therapeutic procedure integrated with surgical practices and bringing several benefits is ozone therapy, a technique that uses ozone gas as a therapeutic agent. Due to the fact that ozone has been correlated with numerous benefits for the treatment of conditions, the present work aims to correlate the clinical experience of its application in the submental region, to improve the condition of fibrosis intercurrence in patients who underwent lipoplasty surgery. There was a significant improvement in the patient’s fibrosis, however, further studies are still needed on the subject, in order to allow well-defined and safe parameters of use.